2005
DOI: 10.1021/np050001a
|View full text |Cite
|
Sign up to set email alerts
|

Bioactive Constituents of the Leaves of Phyllanthus polyphyllus var. siamensis

Abstract: A dichloromethane extract of the leaves of Phyllanthus polyphyllus var. siamensis afforded two new monoacetylated triterpene arabinosides (1 and 2) and 15 known compounds. The structures of the new compounds were elucidated on the basis of spectroscopic data interpretation. The isolates and some chemical transformation products were evaluated biologically, and the presence of an arabinosyl moiety among the hederagenin glycosides evaluated was found to be important for the modulation of cytotoxic activity again… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
10
0

Year Published

2006
2006
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 25 publications
0
10
0
Order By: Relevance
“…Of which Phyllanthus oligospermus a shrub, is one of the most common species found in Taiwan. 1) Members of Phyllanthus have been reported to produce terpenes, 2,3) alkaloids, 4,5) lignans, [6][7][8] flavonoids, 9,10) and tannins 11,12) with diverse biological activities including inhibition of hepatitis B virus, hypoglycemic, hypotensive and diuretic effects and antinociceptive, antitumor, antioxidant, and antiinflammatory properties. Many species of this genus have long been used in the traditional Chinese medicine for the treatment of eye disease, jaundice, headache, eczema, warts, diarrhea, diabetes, hepatitis and dropsy for liver protection and as diuretic.…”
mentioning
confidence: 99%
“…Of which Phyllanthus oligospermus a shrub, is one of the most common species found in Taiwan. 1) Members of Phyllanthus have been reported to produce terpenes, 2,3) alkaloids, 4,5) lignans, [6][7][8] flavonoids, 9,10) and tannins 11,12) with diverse biological activities including inhibition of hepatitis B virus, hypoglycemic, hypotensive and diuretic effects and antinociceptive, antitumor, antioxidant, and antiinflammatory properties. Many species of this genus have long been used in the traditional Chinese medicine for the treatment of eye disease, jaundice, headache, eczema, warts, diarrhea, diabetes, hepatitis and dropsy for liver protection and as diuretic.…”
mentioning
confidence: 99%
“…[19] The genus Phyllanthus contains highly valued medicinal plants which produce a variety of secondary metabolites including flavonoids, phenolic acids, alkaloids, lignans, and tannins, have long been extensively used in folk medicine all over the world. [20] P. polyphyllus has been investigated for their various bioactive properties such as anti-inflammatory, [18] anti-tumour, [21] cytotoxic, [21,22] and hepatoprotective activities. [23,24] Species of these plant genera are used in folk medicine and consumed as healthy ingredients, they could also be useful in preventing mould growth and mycotoxin contamination due to their antifungal properties.…”
Section: Introductionmentioning
confidence: 99%
“…The phytochemical studies of the plant have revealed the presence of benzenoid, 4-0-methyl galic acid, together with three arylnapthalide lignans, namely phyllamyricin, justicidin B and diphyllin. Its extract shows dose-dependent inhibition of inflammatory mediators such as LPS/INF-Y stimulated by peritoneal exuded macrophages (Rao et al, 2006), monoacetylated triterpene arabinosides and terpenes found have cytotoxic activity against human cancer cell lines (Youkwan et al, 2005), antitumor activity against transplantable tumour, protective effect of human umbilical vein endothelial cells against glycated protein-iron chelate induced toxicity (Rajkapoor et al, 2007a(Rajkapoor et al, , 2007b. The present study is aimed to evaluate the protective role of methanol extract of P. polyphyllus against N-nitrosodiethylamine-induced liver tumor in rats.…”
Section: Introductionmentioning
confidence: 99%